Thin Film Transistors For Display Applications: A Review - Mr. Ganesh .V.N, Dr. Shantharama Rai C (International Journal of Advanced Science and Technology, 2020)
Display devices playing vital role in presentation of information in visual, there are plenty of display device technologies are used to represent the visual information in its own way, the electronic display devices are the one prominent area of improvement based on the modern electronic improvements. The technological advancements in the semiconductor industries and the modern physics leads to provide the various improvements in the thin film transistor-based display devises. The uses of TFT based display devices in various electronic gadgets gives the scope of improvements in the solid-state display devices. This paper deals the comparative study of various technologies and the scope of improvement in the thin film-based display devices.